Tatian's Diatessaron : its creation, dissemination, significance, and history in scholarship - Petersen, William Lawrence, 1950-2006. (Vigiliae Christianae, Supplements, 1994)
A gospel harmony composed c. 172 C.E., the Diatessaron is one of the earliest witnesses to the gospels. Regarded as the first version of the gospels in Latin, Syriac, and Armenian, the Diatessaron was used by Encratites, Judaic-Christians, and "Great Church" Christians alike. This study is the first comprehensive treatment of the Diatessaron in more than a century. After sketching the second-century setting and Tatian's biography, it describes virtually every Diatessaronic witness and provides a scholar-by-scholar summary of research from 546 to the present. Criteria for reconstructing Diatessaronic readings are developed, and numerous examples offer the reader first-hand experience with the witnesses. It contains the first Bibliography of research on the Diatessaron (600+ titles) and the first "Catalogue of Manuscripts of Diatessaronic Witnesses and Related Works" ever published.